Intra-Abdominal Hydatid Cyst: Sociodemographics, Clinical Profiles, and Outcomes of Patients Operated on at a Tertiary Hospital in Addis Ababa, Ethiopia. (12th December 2017) - Abebe, Engida; Kassa, Temesgen; Bekele, Mahteme; Tsehay, Ayelign
Abstract : Background . Hydatid cyst is caused by the tapeworm Echinococcus granulosus . The abdomen, specifically the liver, is the most common site affected. Objective . Determine the presentation patterns, types of surgical management, and outcomes of patients operated for intra-abdominal hydatid cyst (IAHC). Methodology . A retrospective descriptive study of patients admitted and operated for IAHC from September 1, 2011, to August 31, 2015. Results . Forty-two patients whose age ranged from 10 to 65 (mean of 37 years) were operated on. Females comprised 27 (64.3%) of the patients. The commonest presenting complaint was abdominal pain (41, 97.6%). Abdominal mass was documented in 23 (54.7%) cases. Abdominal ultrasound (AUS) and CT were the main imaging studies done on 38 (90.5%) and 24 (57.1%) patients, respectively. Cysts measuring more than 10 cm in diameter were the most common finding in both studies. Liver was the primary site involved, 30 (71.4%) cases, the right lobe being the main side, 73%. Thirty-eight (90.5%) patients underwent deroofing, evacuation, marsupialization, and omentoplasty (DEMO). There was no perioperative death, but 4 (9.5%) of the patients had post-op complications. Conclusion . Abdominal pain was the most common presenting complaint. AUS and CT remain the preferred imaging. DEMO was the most common surgery.